Islamic Book and Islam in Indonesia: a Historical Perspective - Jajat Burhanudin (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
Alongside the advance of Islamic reformism in the early twentieth century, one central element to pay attention is the rise of printed media, Islamic book, which enhanced the shaping of the reformist Muslims. Written in Malay with Rumi script, the books with Islamic substance first appeared as part of Islamic reform movement. Nearly all the authors were the leading activists of reformist organizations. This trend continued to develop, leading the books to emerge as an important pillar in the formation of Islamic intellectual discourses. This study focuses on the historical study of the Islamic books development and progression, with strong emphasis given to the ideas behind their rising in the courses of Indonesian history. Based on the classical theory of discourse of Michel Foucault, as well as the one of post-linguistic turn historiography, this article demonstrates, in reference to the three time periods which each presented a specific mode of intellectual thinking, the growing importance of Islamic books in the making of print-based religious life, which paved the way for the strengthening of socio-religious plurality in modern Indonesia. Firstly, Islamic Book as the voice of Islamic reform, secondly, Islamic Books in 1950s-1960s, and lastly, Islamic Books in contemporary Indonesia.